Intensive Care Management of Patients with COVID-19 - Eka Ari Puspita; Muhammad Afif (PROCEEDING UMSURABAYA, 2023)
Abstract               The Covid-19 infection, which has become a pandemic, is a challenge for doctors in carrying out treatment. This is because the pathophysiology of Covid 19 is very complex. This disease not only affects the lungs but also other organs. Symptoms also vary from asymptomatic patients to those with severe symptoms. In COVID-19 patients with severe symptoms, treatment in the ICU is required. Treatment in the ICU requires very complex monitoring and therapy which until now do not have the same standard.Keywords: COVID-19, Intensive Care Unit, Mekanic Ventilation